30. The UPIC System of Iannis Xenakis: Autoethnography as Rapprochement - Peter Nelson (Meta-Xenakis: New Perspectives on Iannis Xenakis’s Life, Work, and Legacies, 2024)
Drawing on the author’s experience of working with Les Ateliers UPIC between the presentation of the UPIC computer music system at the Huddersfield Festival of Contemporary Music in 1987, and its residency at the International Computer Music Conference (ICMC) 1990, this paper will reflect on the technological, educational, social, and organizational milieu of UPIC during the period of its formation as both a material equipment, and a cultural project. As well as interrogating historical anecdote, this chapter attempts to contextualize UPIC within a set of cues taken from recent work in science and technology studies–particularly the work of Antoine Hennion–as well as from Howard Becker’s classic sociological investigation of ‘art worlds’, in order to clarify both the historical impact and the possible future potential of Xenakis’s conception. Beginning in an era when institutional infrastructure was a necessity for any project of this kind, UPIC has morphed, in the subsequent era of internet sociality, into an app with a contrasting set of technical and operational consistencies. This contrast will be considered as a key means of insight into the creative conceptions that underpin UPIC as part of an attempt to reassess the position of the system within Xenakis’s main theoretical achievement and creative output.